Four Seasons a Silang winery and events venue - Dolor, Monina Victoria; Tomeldan, Michael V. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The Philippines is not known as a wine-producing country and you will most likely not hear the country's name roll off the tongue of a sommelier - however, Silang's distinctive climate and culture contributes to continued local wine production. Tours of wineries are not even easy to find in the Philippines. Perhaps through Four Seasons : A Winery and Events Venue, the wine industry will continue to progress with its own unique way of experiential wine tourism. With the vastness of greenery, Four Seasons will serve as a catalyst to introduce the history and culture of Silang, Cavite. It will improve agricultural activities through the use of locally produced fruits for the winery with the help of technology. It will give an opportunity for further developments to commence in the town. Furthermore, its potential of being the Food Basket Capital of Cavite will be enhanced with local civic pride and community involvement. As the development caters to tourists and locals, it also aims to tell the story of Silang, Cavite and the story of wine-making. It is for these people to witness the tale it wants to tell. All wines have a tale to tell, but that only the best wines have the best stories.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Wine tourism; Wine tourism -- Cavite -- Philippines